Smartphone addiction and malevolent creativity—the mediating role of psychological capital and the moderating role of self-concept clarity - Li, Wei; Zhou, Ying (Frontiers in Psychiatry, 2025)
PurposeThis study examines the correlation among smartphone addiction (SA) and malevolent creativity, as well as the underlying mechanisms involved. A moderated mediation framework was established to investigate the impact of SA on malevolent creativity in college students, taking into account the mediating influence of psychological capital and the moderating effect of self-concept clarity (SCC).MethodThis survey was conducted from May 10 to August 15, 2024 at a higher education institution in a central city of China. A total of 1,091 Chinese college students completed measuring SA, psychological capital, SCC, and malevolent creativity. Correlation and mediational moderation studies were performed utilizing SPSS (version 25.0) and AMOS (version 23.0).ResultsThe association research indicated that SA exhibited a beneficial association with malevolent creativity and SCC, while demonstrating an adverse relationship with psychological capital. Additionally, malevolent creativity had an adverse association with psychological capital and positively and a good correlation with SCC. Furthermore, psychological capital was negatively correlated with SCC. The structural equation modeling investigation indicated that SA directly predicts malevolent creativity in college students, but psychological capital exerts an indirect predictive influence between the two variables. Specifically, psychological capital was found to be a partial mediator and buffer between SA and malevolent creativity. In addition, SCC moderated the second half of the “smartphone addiction →psychological capital → malevolent creativity” path and moderated the “smartphone addiction → malevolent creativity” path.ConclusionSA directly and indirectly affects malevolent creativity through psychological capital. SCC serves as a mitigating factor between SA and malevolent creativity. The association between psychological capital and malevolent creativity is great when the degree of self-concept is elevated, whereas the correlation between SA and malevolent creativity is also rather substantial.